Subcutaneous tissue expansion and subsequent subpectoral implantation for breast reconstruction in Asian patients: safety and outcome - Engel, Holger; Huang, Jung-Ju; Lin, Chia-Yu; Lam, Wee Leon; Gazyakan, Emre; Cheng, Ming-Huei (Annals of plastic surgery, 2013)
Asian women are generally thin with smaller breasts. The objective was to investigate the outcomes for patients who underwent 2-stage breast reconstruction using subcutaneous expansion followed by subpectoral implantation. Between 2003 and 2008, 22 patients underwent subcutaneous expansion and subsequent submuscular implantation for 23 breast reconstructions. Mean age was 44.6 ± 7.0 years. The outcome was assessed with a pain visual analog scale, a questionnaire, and the cosmesis. Mean expansion volume was 350.3 ± 80.8 mL. Mean implant size was 306.7 ± 84.6 mL. The complication rate was 8.6%, 13.0% in first and second stages. Mean pain scale was 2 ± 1.4. At a mean follow-up of 42.5 ± 18 months, patient's satisfaction was 3.2 ± 0.9. Overall shape of the reconstructed breast was rated as 2.8 ± 0.5. Subcutaneous expansion with subsequent subpectoral implantation is feasible and reliable in low body mass index, nonsmoking, nonradiated patients with small and projective breasts.
Gesehen am 05.02.2021